SPECTRUM OF MALARIA IN HAJJ PILGRIMS IN THE YEAR 2000 - Khan, Abdus Salam; Qureshi, Fayaz; Shah, Arif Hussain; Malik, Salman Akbar (Journal of Ayub Medical College Abbottabad, 2002)
Background: This study was carried out to investigate the country wise distribution of malarial parasite in Muslim pilgrims. Methods: This study was conducted at Ajyad Hospital, Makkah Al-Mukarmah, Saudi Arabia during peak Hajj season, from February to March 2000. The peripheral blood smears for malarial parasites were examined from one hundred and thirty patients suspected to be suffering from malaria. Results: A positive identification of malarial parasite was possible in 19.2%. Seventy-six percent patients were suffering from Plasmodium falciparum infection, while 24% had Plasmodium vivax infection. Fifty percent of patients from Sudan and Saudi Arabia had P. vivax malaria while in the rest of the countries only P. falciparum infection was found. The patients presented with protean clinical manifestations. Conclusions: Malaria is prevalent in many Muslim countries and the frequency of falciparum species seems to increase as compared to vivax malaria. The majority of falciparum malaria patients develop haematological complications. Key Words: Muslim countries, pilgrims, malaria, plasmodia, hemolysis